Théâtre et cinéma dans les territoires occupés de Russie à travers la presse collaborationniste (1941-1944) - Boris Kovaliov (Conserveries Mémorielles)
This article discusses how durng 1941-1944 the Nazis delivered propaganda through the theatre and cinema in the occupied territory of one of the Soviet republics with the predominant Russian population. Theatres and cinemas, organised and opened by the Nazis in the occupied territory, were not simple propaganda structures. Frequently, the civilian population pecieved it as a form of entertainment. To consider the effectiveness of this phenomenon, it is required to analyse the process of opening various theatres and cinemas and their repertoire. It is extremely important to identify the proportion of timeless classic works to anti-Soviet, anti-Semitic and Nazi-oriented films, programs, and performances. Some approaches of the Soviet and Nazi propaganda were quite identical. Moreover, some Russian collaborators had practical work experience in Soviet cultural institutions in the pre-war period.It is also necessary to determine the effectiveness of this form of propaganda activities and to identify its reflection in the Russian-language collaborationist press.